Environmental Projects Management (on the Example of the “Green Oasis” Urban Garden Project) - Yu, Aihua (Lesya Ukrainka Volyn National University, 2024)
This master’s thesis is dedicated to the management of environmental projects using the example of the creation of the “Green Oasis” urban garden. The first chapter examines the theoretical and methodological foundations of project management in the environmental sphere, including the essence and types of environmental projects, current trends in the management and implementation of such projects, and methodological aspects of management. The second chapter analyzes the provision of the implementation of the environmental project for the creation of the “Green Oasis” urban garden, including problem analysis and project idea development, formulation of the project’s goals and objectives, and risk management. The third chapter develops the project planning system, including the summary and strategy development of the project, budget planning, evaluation of effectiveness, and project scaling. The work concludes with findings on the effectiveness of environmental project management and recommendations for further implementation of similar initiatives. The significance of such projects as “Green Oasis” lies in their impact on the urban environment and community. They contribute to improving the quality of life for city residents by creating new recreational areas, raising environmental awareness, and fostering a healthier and more comfortable urban environment. Additionally, such projects can be an essential element of a city’s sustainable development strategy, attract investments, support the local economy, and serve as a model for similar initiatives in other cities and regions.
Keywords: environmental projects; urban garden; project management; budget planning; risk management